2018
DOI: 10.1007/s10943-018-0657-4
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Nurses in Turkey Toward Care of Dying Individual and the Associated Religious and Cultural Factors

Abstract: The aim of this study was to determine the attitudes of nurses working in two university hospitals located in the west and east of Turkey toward care of dying individual as well as religious and cultural factors that influence their attitudes. The descriptive and comparative study was conducted with a total of 189 nurses who were working in adult inpatient clinics of two university hospitals in western (101 nurses) and eastern (88 nurses) Turkey between July and November 2016. The data were obtained by using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 13 publications
4
32
1
2
Order By: Relevance
“…This study showed that the overall attitudes toward hospice care score, median 102.00(interquartile range, 95.5-120.50), among front-line nurses was higher than that found in studies by Karadag et al (Mean ± SD, 97.19 ± 8.99) 20 and Lancaster et al (Mean ± SD, 101.45 ± 15.99) 21 but lower than that found in the study by Ho et al (Mean ± SD, 116.8 ± 11.4). 22 Therefore, the nurses’ attitudes toward hospice care was moderate.…”
Section: Discussioncontrasting
confidence: 70%
“…This study showed that the overall attitudes toward hospice care score, median 102.00(interquartile range, 95.5-120.50), among front-line nurses was higher than that found in studies by Karadag et al (Mean ± SD, 97.19 ± 8.99) 20 and Lancaster et al (Mean ± SD, 101.45 ± 15.99) 21 but lower than that found in the study by Ho et al (Mean ± SD, 116.8 ± 11.4). 22 Therefore, the nurses’ attitudes toward hospice care was moderate.…”
Section: Discussioncontrasting
confidence: 70%
“…In comparison to Western countries, Korean people are less likely to discuss death or dying situations, due to the belief that it is a failure on their part, as well as the traditional Korean view of death by a Confucian society, where people tend to extend meaningless life-prolonging treatment [4,35]. For this reason, different cultural backgrounds of nurses can be also considered as a contributing to positive or negative perceptions and attitudes [31,37].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses need to know physical and psychological needs of the patients, to develop a positive attitude toward death, and to accept death to provide better health care. A nurse who does not have a positive view of death and does not accept that death is a part of life may have negative emotions and behaviors when he or she encounters with death (Karadag et al., 2019). Nurses who find encounters with death and dying very difficult may undergo feelings of insufficiency, helplessness, defensiveness, or distress; and coping mechanisms, such as prevention, being distant, and avoidance may be adopted (Anderson, Kent, & Owens, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the main aim to care for dying patients is to provide the patients with physical and spiritual relief, to increase their quality of life, such as through spending good times without pain, through the end of life, and to prepare them for death (Gurdogan et al., 2017). Health professionals need to be well prepared in knowledge, skill, and attitudes to be able to provide dignified end-of-life care (Guo & Jacelon, 2014; Karadag et al., 2019). Nurses reported regret when unable to provide a “good death” for a patient (Cottrell & Duggleby, 2016, p. 709).…”
Section: Discussionmentioning
confidence: 99%